4-Benzyl-3-(2-furyl)-1H-1,2,4-triazole-5(4H)-thione hemihydrate - Zareef, Muhammad (International Union of Crystallography, 2008)
In the asymmetric unit of the title compound, C(13)H(11)N(3)OS·0.5H(2)O, there are two independent molecules of 4-benzyl-3-(2-furyl)-1H-1,2,4-triazole-5(4H)-thione and a water molecule of hydration. The conformation of the two organic molecules is slightly different, the dihedral angles formed by the furyl and triazole rings being 5.63 (15) and 17.66 (13)°. The water molecule of hydration links three adjacent triazole molecules to form a cluster via intermolecular O—H⋯S, N—H⋯S and N—H⋯O hydrogen bonds, generating a 10-membered ring of graph set R (3) (3)(10). The crystal structure is further stabilized by intra- and intermolecular C—H⋯S, C—H⋯O and C—H⋯N hydrogen bonds and by π–π stacking interactions involving the furyl and triazole rings of centrosymmetrically related molecules, with a centroid–centroid separation of 3.470 (2) Å.